Fuzzy Cone Normed Linear Space and Some Fixed Point Results for Weakly Compatible Mappings - Tamang, P.; Bag, T. (Communications in Mathematics and Applications, 2021)
In this paper, an idea of fuzzy cone normed linear space is introduced with underlying space is Felbin’s type fuzzy Banach space. Some basic results as well as results in finite dimensional fuzzy cone normed linear space are studied. Lastly, some fixed point theorems for weakly compatible mappings are established in such spaces.